Parámetros reproductivos y productivos en cuyes peruanos mejorados (Cavia porcellus.L.) Alimentados en leguminosas tropicales y banano maduro (Musa paradisiaca - Alcívar Loor, Raúl Edison (2011)
The present investigation was executed in the Area of Species smaller than the Experimental Property "The María" of property of the State Technical University of Quevedo (UTEQ), located in the kilometer 71/2 of the via Quevedo-the Connection, county of The Ríos. Located among the geographical coordinates 700 27' 13 '' of latitude west and 010 06' 02 '' of south latitude, to a height of 70 msnm. The field work had a duration of 120 days. The objectives were: to) to Determine the leguminous one tropical (Pueraria phaseoloides (Roxb) Benth) and Gliricidia sepium) and the appropriate level of mature banana tree (100; 125; 150 g animal-1 day-1), during the reproduction phases and production, respectively) that allows to increase the reproductive and productive parameters in improved Peruvian guinea pigs. b) to Determine the best relationship benefit-cost in the treatments. In the reproduction phase a factorial arrangement was applied 2 (leguminous tropical forrajeras) x 3 (levels of mature banana tree) + 1 (witness), inside a Design of Complete Blocks at random (DBCA) with four repetitions, equal arrangement and experimental design was applied in the phase of it puts on weight, the experimental unit was conformed by two animals. To determine differences among treatment stockings, was the test of multiple ranges of Tukey applied (P> 0,05). For the economic analysis of the treatments the Relationship Benefit-cost was applied. In the first phase 56 female guinea pigs of five months of age were used with a weight average of 700g, in second o'clock 56 blunders of 21 days of age they were used, with a weight average of 300g. The experimental units were placed in wire cages galvanized with their respective metallic troughs and drinking troughs automatic sucking type. The tropical kudzu was the leguminous of more consumption (P <0,01) during the reproduction stages and production (162,54 and 96,29 g MS animal-1 day-1). In a same way in the reproduction stage the tropical kudzu allowed to increase (P <0,01) the weight of the female to the 30 days posmonta (1303,42 g), I weigh from the female to the childbirth and the weaning (1148,75 and 1109,50 g), I weigh from the litter to the birth (350,92 g), I weigh and size of the litter to the weaning (781,58 g and 2,29, respectively). The tropical kudzu allowed to increase (P <0,01) in the production phase (it puts on weight) the consumption of total food, alive weight (980,91 g), gain of weight (9,29 g animal-1 day-1), I weigh to the channel (697,16 g), yield to the channel (71,11%). The levels of mature banana tree didn't affect (P>0,05) the variables evaluated in the stages re reproduction and production. The biggest profitability in the production stage obtained it to him when combining tropical kudzu more 125; 150 and 100 g of mature banana tree animal-1 day-1 (37,96; 35,27 and 34,31%, respectively). Key words: Forrajeras, arbustivas, kudzu, matarratón, feeding, guinea pigs.